Do Political Connection and Corporate Governance Mechanism Increase Corporate Social Responsibility Disclosure? - Yeterina Widi Nugrahanti (Politeknik Negeri Bandung, 2021)
The objective of this study is to investigate the impact of political connection and corporate governance mechanisms (independent board of commissioner, institutional ownership, and board of commissioner size) toward Corporate Social Responsibility (CSR) disclosures using Global Reporting Initiative (GRI) Guidelines. Purposive sampling technique was conducted and 272 non-financial companies listed in the Indonesian Stock Exchange during 2015-2017 were acquired as the samples (816 firm-years). For testing the hypotheses, unbalanced Generalized Least Square panel data regression was employed. The finding shows that political connection and board of commissioner size have a positive impact on CSR disclosures while independent board of commissioner and institutional ownership do not. This study contributes to political connection, corporate governance mechanism, and CSR disclosure literature by identifying CSR disclosure based on GRI guidelines up to the most detailed level, which are 77 disclosure items indicators and 254 sub-indicators. Meanwhile, previous research only identify CSR disclosure up to 77 GRI indicators without paying attention to the sub-indicators in detail.